If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x + 5) = 6(x + 5) + -8 Reorder the terms: f(5 + x) = 6(x + 5) + -8 (5 * f + x * f) = 6(x + 5) + -8 (5f + fx) = 6(x + 5) + -8 Reorder the terms: 5f + fx = 6(5 + x) + -8 5f + fx = (5 * 6 + x * 6) + -8 5f + fx = (30 + 6x) + -8 Reorder the terms: 5f + fx = 30 + -8 + 6x Combine like terms: 30 + -8 = 22 5f + fx = 22 + 6x Solving 5f + fx = 22 + 6x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Reorder the terms: -22 + 5f + fx + -6x = 22 + 6x + -22 + -6x Reorder the terms: -22 + 5f + fx + -6x = 22 + -22 + 6x + -6x Combine like terms: 22 + -22 = 0 -22 + 5f + fx + -6x = 0 + 6x + -6x -22 + 5f + fx + -6x = 6x + -6x Combine like terms: 6x + -6x = 0 -22 + 5f + fx + -6x = 0 The solution to this equation could not be determined.
| -14x-83=-8x-47 | | x-(3-x+1)=#-6 | | 3x+21=2x+13 | | f(x+5)=6x-8 | | 2(n+.3333333333333)=1.666666666666n+1+.5n-.33333333333 | | 4(x-2)=2(x-4)+2 | | 3-7y+4=2y+11-7y | | 120(20)=50(x) | | (2(3)-a)(3+b)(3+c)=0 | | x-(3-x+1)=-x-4 | | x-3(-x+1)=-x-4 | | f(x)=1+ln(1+ln(1+ln(1+x))) | | 19-(5m+7)=4+2m-13 | | 60(36)=60(k) | | (2b-1)i+(a+3)=4-8i | | 4t^2-20t-25=0 | | (3x-5)+(12x)=90 | | (3-2i)-(2x+yi)=7+6i | | 3a-10+4a=5a-7 | | 3.7b+7=8.1b-18.4 | | 42(z)=35(28) | | 4+3+-7=4+-7 | | 36(x)=45(32) | | (2x)=(2y-x) | | (3x-5)=(12x) | | C(x)=.6x+30 | | x-3(-x)+1=-x-6 | | 18(5)=7.5(x) | | 10-(3x-5)=11-4x | | 8+3x=132 | | 10x-50=7x-20 | | x-(3-x+1)=-x-6 |